TECHNOLOGIES FOR THE DEVELOPMENT OF BIOPOLYMERS, AS AN ALTERNATIVE IN THE SUBSTITUTION OF PLASTIC (PET) - Alucho-Pasto, Josselin (2021)
The excessive use of PET (polyethylene terephthalate) plastic and its harmful environmental impact has caused an increasing demand for sustainable alternatives for the production of bioplastics, for this reason it is essential to determine materials that guarantee the required physical properties, promoting the research and development of new environmentally friendly products. Biopolymers produced from starches are biodegradable compounds that can be used for the production of product packaging due to the characteristics they present, which guarantee health, quality, and conservation. Which, investigations have been carried out to apply different technologies, for the use of potato starch, cassava, corn among others.